2020
DOI: 10.1093/ej/ueaa038
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Indirect Effects of Adverse Employer Behaviour on Worker Productivity: a field Experiment

Abstract: We conduct a field experiment to study how worker productivity is affected if employers act adversely towards their co-workers. Our employees work for two shifts in a call-center. In our main treatment, we lay off some workers before the second shift. Compared to two control treatments, we find that the layoff reduces the productivity of unaffected workers by 12%. We find suggestive evidence that this result is not driven by altered beliefs about the job or the management's competence, but caused by the worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Furthermore, we have found that a discriminatory payment procedure leads to similar overall performance as a competitive payment procedure. Other studies have shown that wage differentials arising from perceived unfair procedures can result in less effort exerted at the workplace (e.g., Cohn et al 2014; Heinz et al Forthcoming; Johnson and Salmon 2016; McGee and McGee 2019). Maybe due to the one‐shot nature of our experiment, we did not observe any effects on workers' motivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have found that a discriminatory payment procedure leads to similar overall performance as a competitive payment procedure. Other studies have shown that wage differentials arising from perceived unfair procedures can result in less effort exerted at the workplace (e.g., Cohn et al 2014; Heinz et al Forthcoming; Johnson and Salmon 2016; McGee and McGee 2019). Maybe due to the one‐shot nature of our experiment, we did not observe any effects on workers' motivation.…”
Section: Resultsmentioning
confidence: 99%
“…When institutions violate procedural‐fairness norms, people may refuse to accept unequal outcomes (Grimalda, Kar, and Proto 2016), may engage in cheating (Gill, Prowse, and Vlassopoulos 2013), lying (Banerjee, Gupta, and Villeval 2018), sabotage (Ambrose, Seabright, and Schminke 2002; Fehr 2018), or theft (Greenberg 1990) in retribution. Moreover, procedural unfairness at the workplace can lower workers' intrinsic motivation (e.g., Breza, Kaur, and Shamdasani 2018; Cohn et al 2014; Gächter and Thöni 2010; Heinz et al Forthcoming), work satisfaction (Breza, Kaur, and Shamdasani 2018), and labor supply (Bracha, Gneezy, and Loewenstein 2015). In contrast to the aforementioned studies, we do not focus on antisocial behavior as a retributive justice motive, or on situations in which it is individually beneficial to act unethically.…”
Section: Introductionmentioning
confidence: 99%
“…3 A consequence of the insurance component is that the agent absorbs part of the shock. If the principal is risk-neutral and the agent is risk-averse (as is typically assumed in the principal-agent literature) then this leads to inefficiencies not considered in the present paper.4 Indeed, a number of recent studies show that the breach of the implicit agreement in a reciprocal relationship can cause long-lasting adverse effects (see(Heinz et al, 2020;Friebel et al, 2017), among others).…”
mentioning
confidence: 89%
“…Della Valle and Ploner (2017) replicate this finding and argue that this behavior aims at restoring one's own subjective fairness balance. This suggests, however, that generalized negative reciprocity is not driven by the intention to hurt someone, and, hence, perceived interactional injustice might not trigger counterproductive work behavior toward coworkers―especially because employees seem to care for the well‐being of even unknown coworkers by punishing their employer with reduced performance after layoffs (Heinz et al, 2020).…”
Section: Related Literaturementioning
confidence: 99%